2023
DOI: 10.1038/s41598-022-27090-1
|View full text |Cite
|
Sign up to set email alerts
|

Zoledronic acid targets chemo-resistant polyploid giant cancer cells

Abstract: Although polyploid giant cancer cells (PGCCs) are known as a key source of failure of current therapies, sufficient drugs to target these cells are not yet introduced. Considering the similarities of polyploid cells in regeneration and cancer, we hypothesized that zoledronic acid (ZA), an osteoclast-targeting agent, might be used to eliminate PGCCs. The 5637-bladder cancer cell line was treated with various doses of cisplatin to enrich polyploid cells and the efficacy of different concentrations of ZA in reduc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Beyond radiation therapy, multinucleated giant cells implicated in diseases like schistosomiasis, sarcoidosis, and arthritis require substantial energy for their formation, especially for membrane fusion and cytoplasmic expansion, thereby necessitating increased glucose uptake 19 . Additionally, chemotherapy-induced polyploid giant cancer cells undergo significant metabolic shifts post-treatment, indicating altered metabolic pathways, including those related to glucose metabolism 20 . These insights highlight the broader metabolic requirements of giant cells, underscoring their adaptive responses to diverse stressors.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond radiation therapy, multinucleated giant cells implicated in diseases like schistosomiasis, sarcoidosis, and arthritis require substantial energy for their formation, especially for membrane fusion and cytoplasmic expansion, thereby necessitating increased glucose uptake 19 . Additionally, chemotherapy-induced polyploid giant cancer cells undergo significant metabolic shifts post-treatment, indicating altered metabolic pathways, including those related to glucose metabolism 20 . These insights highlight the broader metabolic requirements of giant cells, underscoring their adaptive responses to diverse stressors.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent review, we proposed an analogy between the function of polyploid cells in cancer and regeneration [ 29 ]. In line with this concept, we found zoledronic acid that is an osteoclast targeting agent to be effective in eradicating PGCCs originated from bladder cancer cells [ 34 ].…”
Section: Introductionmentioning
confidence: 89%
“…155 PGCCs are rich in mitochondria, which support the survival of cancer cells by producing ATP. Adibi et al 156 reported increased lipid droplet formation has been observed in PGCCs. Lipids likely serve as energy stores that help PGCCs endure stress.…”
Section: 3mentioning
confidence: 97%
“…This indicates that targeting lipid metabolism in PGCCs may represent a promising strategy for overcoming chemoresistance and improving the success rate of cancer treatment. 156 (4) Induced-differentiation. PGCCs cultured in medium containing 3-isobutyl-1-methylxanthine, insulin, dexamethasone and rosiglitazone can be induced to transdifferentiate into mature functional adipocytes.…”
Section: Potential Therapeutic Strategy For Targeting Pgccsmentioning
confidence: 99%
See 1 more Smart Citation